Decoding University Choices: Assessing the Impact of Customer Relationship Management on Decision-Making - Marwan Effendi; Andi Primafira Bumandava Eka; Desman Serius Nazara; Cucu Hodijah; Tonny Yuwanda (Jurnal Aplikasi Manajemen)
Business competition does not only occur in a company. Universities also compete with each other to get students. A strategy is needed to strengthen the attractiveness of institutions amidst increasingly tight competition. This study aims to identify factors that influence students' decisions in choosing universities in West Java, with an emphasis on the role of Integrated Marketing Communications, Customer Relationship Management, and Service Quality. The survey method was conducted online and offline on 561 respondents, with 243 respondents meeting the criteria. Data collection was conducted through a validated questionnaire. The results of path analysis showed a significant relationship between Integrated Marketing Communications and Customer Relationship Management with students' Choice Decisions. However, although Service Quality did not have a significant direct relationship with Choice Decision. This study also highlights the importance of maintaining high service standards to maintain student satisfaction. Moderating the effect of gender on the relationship between service quality, the choice decision implies that the university should harness a gender-related approach.